Colonic Angiosarcoma Arising in Association with Amyloid Deposits. (16th May 2020) - Said, Samar; Graham, Rondell P.; Wu, Tsung-Teh; Yasir, Saba; Zhang, Lizhi; Folpe, Andrew L.
Abstract : Angiosarcoma of the colon is rare, as is colonic amyloidosis. To our knowledge, there have been no reported cases of angiosarcoma arising in association with amyloid deposition. Herein, we described a case of 77-year-old man who presented with hematochezia, and a sigmoid mass was found on colonoscopy. Histologic examination of the resected specimen showed extensive nodular deposition of AL-lambda amyloid material in the colonic wall, as well as high-grade angiosarcoma which was closely intermingled with the amyloid deposits. While the occurrence of both colonic amyloidosis and angiosarcoma in this patient may represent pure coincidence, given the intimate association of the angiosarcoma and the amyloid deposition and the rarity of both of these lesions, we hypothesize that angiosarcoma could be secondary to amyloid deposition.